Corporate Governance and Performance of Firms Listed on the Nairobi Securities Exchange - Kobuthi, Edward; K’Obonyo, Peter; Ogutu, Martin (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to establish the effect of corporate governance on performance of firms listed on the Nairobi Securities Exchange (NSE). The author developed a corporate governance index as a proxy for corporate governance based on the seven attributes of the recently revised Capital Markets Authority (CMA) draft code of corporate governance practices for public listed companies in Kenya. The guidelines cover board operations and control, rights of shareholders, stakeholder relations, ethics and social responsibilities, accountability, risk management and internal audit, transparency and disclosure and supervision and enforcement. The survey questionnaire was the main tool of data collection and was distributed to 56 CEOs and corporation secretaries. The response rate was 87.5%. Annual reports for 2015 were used to compute the CGI score for the different organizations. The study found a statistically significant relationship between corporate governance and non-financial performance of firms listed on the Nairobi Securities Exchange confirming that organizations can enhance their performance by implementing good corporate governance, specifically those attributes of good corporate governance that matter.